Construction of Lactobacillus acidophilus expression vector and expression of mannanase - GU Bintao, GUO Jianjun, ZENG Jing, NIE Junhui, WANG Tong, XIONG Dawei, YUAN Lin (Zhongguo niangzao)
In order to obtain mannanase-producing Lactobacillus acidophilus strain, the mannanase expression vector was constructed and transformed into L. acidophilus. The enzymatic properties of mannanase produced by recombinant L. acidophilus were analyzed, and the acid resistance of recombinant L. acidophilus and anti-protease activity of mannanase were determined. The results showed that the mannanase activity produced by recombinant L. acidophilus was 353 U/ml after fermentation for 24 h. The optimum catalytic pH and temperature of mannanase was 5.5 and 55 ℃, respectively. The recombinant L. acidophilus had certain acid resistance at pH 2.0 to 4.5, and the survival rate was 77.3% at pH 2.0 for 2 h. After mannanase solution was treated with pepsin and trypsin for 160 min, the relative activities of mannanase were 65% and 28%, respectively. The results indicated that the mannanase had certain anti-pepsin and partial anti-trypsin degradation ability.